Study of the Incidence of Bacteria that Cause Tonsillitis and their Sensitivity to Drug Treatment - Jolan, Rehab Gheni; Abdulhasan, Rawaa Sahib; Mohsein, Osama A. (American Journal of Biology and Natural Sciences, 2024)
Background; Tonsillitis, also referred to as inflammation of the tonsils, is a prevalent condition that accounts for approximately 1.3% of outpatient visits. When uncomplicated, it manifests as a sore throat; it is typically the result of a viral or bacterial infection. Aims of the study; To identify the bacterial species associated with tonsillitis in different age groups and to identify the most effective antibiotics. Methodology; A retrospective study analyzed 1000 throat swab samples (500 men and 500 women) from patients with tonsillitis at Al-Habobbi Teaching Hospital between January 1, 2024, and February 10, 2024. Throat swabs were collected and analyzed using standard microbiological techniques, including microscopy, culture on blood, MacConkey, and chocolate agars, and biochemical tests for bacterial identification. Antibiotic susceptibility was assessed using Mueller-Hinton agar and various antibiotic discs. Result; The study included 1000 samples evenly divided by gender and age group. Fever (60%) was the most common symptom, followed by difficulty swallowing (40%), bad breath (30%), and loss of appetite (50%). Streptococcus pyogenes was the most common bacteria (40%), followed by Staphylococcus aureus (25%) and Haemophilus influenzae (15%). Sensitivity tests showed high effectiveness of penicillin (85%) and amoxicillin (90%) against Streptococcus pyogenes, while Staphylococcus aureus had 75% sensitivity to ciprofloxacin. Significant statistical variation was noted in bacterial frequencies and antibiotic sensitivity. Conclusions; Streptococcus pyogenes is the predominant bacterium causing tonsillitis, with high sensitivity to penicillin and amoxicillin. Fever and difficulty swallowing are common symptoms. The variability in antibiotic sensitivity underscores the need for tailored treatments and resistance monitoring.